Architecture based on Microservices and DevOps for continuous software engineering - Mamani Rodríguez, Zoraida Emperatriz (2020)
Microservices are conceived as an architectural style focused on developing applications through a set of services, independent, scalable, collaborative, evolutionary, capable of adapting to complex ecosystems. On the other hand, DevOps is a paradigm that uses a set of principles focused on the continuous delivery and integration of software, this implies a new culture to develop and deploy software in highly collaborative and agile contexts aimed at reducing the gap between development and operations. It is in this context that the present work proposes an Architecture based on Microservices and DevOps for continuous software engineering and applies the proposal through a case study with the participation of development teams formed by the students of the Workshop courses of Software and Systems Construction of the academic semesters: 2018-1, 2018-2, 2019-1, 2019-2 and led by the authors of this research; As a result of value there is a software product consisting of a set of Apps implemented with leading stack technologies under a disruptive approach.